The Soybean Botany, Production and Uses - Singh, Guriqbal (CABI, 2014)
The protein content in soybean (Glycine max(L.) Merrill) seed is approximately 40% and the oil content is approximately 20%. This crop has the highest protein content and the highest gross output of vegetable oil among the cultivated crops in the world. In 2007, the total cultivated area of soybean in the world was 90.19 million ha and the total production was 220.5 million t (FAO, 2009). The origin of soybean cultivation is China. China was the world’s largest soybean producer and exporter during the first half of the 20th century. In the 1950s soybean production developed rapidly in the USA, and the USA is now the largest soybean-producing country in the world. In the 1970s soybean production developed in Brazil, and this country is now the second largest soybean-producing country. Since then, soybean production deve loped rapidly in Argentina, now the third major soybeanproducing country. These soybean-producing countries use machines in commercial production and the commodity rate of soybean is high. They are therefore not only large producers of soybean, but also large exporters. Soybean production in India is developing rapidly and the cultivated area of soybean is about the same as in China, but the yield per unit area is still relatively low.